New Mimesis: Introduction - Impett, Jonathan (2023)
As the relevance and utility of compositional models and techniques derived from existing music theory seemed to some composers to be dissolving at the end of the nineteenth century, they turned to other sources for paradigms of musical thought. Mahler effectively turned to phonography, as did Ives. Schönberg could be seen as having turned to symbolic logic, the kind of thinking being developed by Russell, Frege and then the Vienna Circle. One approach is more empiricist, the other more formalist, to use Badiou’s characterisation (Badiou 2007, 11). In neither case is the ‘model’ used literally; what we often see in music and sound is mimesis of the mimetic technique. New models of morphology and geometry are fundamental to the transformation of materials in Varèse; lines become surfaces, changing perspective as the move through space.
FRIS
1
Keywords: Music, Thought and Technology